Trust and Romantic Relationship Quality as Serial Mediators of Link Between Partner Phubbing and Relationship Satisfaction - Dogru, Muhammet Can; Oge, Ramazan Mert; Satici, Seydi Ahmet; Deniz, Mehmet Engin (SAGE PUBLICATIONS INC, 2025)
Excessive use of mobile devices is changing interpersonal relationships. In particular, smartphones have an impact on all aspects of individuals' lives, and romantic relationships are also affected. Therefore, it is imperative to examine these effects in the context of romantic relationships. This study examined the effect of partner phubbing on relationship satisfaction and the mediating role of trust and romantic relationship quality among individuals in romantic relationships. Data were collected from 361 Turkish adults (269 women, 92 men; 18-50 years old). Results showed that partner phubbing directly and negatively predicted trust and romantic relationship quality. According to structural equation modeling, trust and romantic relationship quality fully mediated the relationship between partner phubbing and relationship satisfaction. In other words, when individuals are exposed to partner phubbing, their trust in each other may decrease, and decreased trust may decrease perceived romantic relationship quality. A decrease in romantic relationship quality negatively affects relationship satisfaction. Results are discussed in light of existing knowledge about partner phubbing, trust, romantic relationship quality, and relationship satisfaction.
Keywords: Partner phubbing; trust; romantic relationship quality; relationship satisfaction; structural equation modeling; PHONE; CONVERSATION; PREDICTORS; COMMITMENT; COUPLES; SCALE; ME; Psychology